Learning Ecology Perspective of Instructors to Enhance EFL Students' Speaking Skills: a Microsystem Perspective of Bronfenbrenner's Bioecological Model - Rahimi, Mahmood (Vision: Journal for Language and Foreign Language Learning, 2023)
Learning ecology is considered a practical part of language learning, particularly speaking skills. In applicable terms, understanding ecological perspectives assists students in practicing speaking and other language skills better. Given the significance of learning ecology, this study investigates EFL instructors' perspectives on learning ecology to boost students' speaking skills using a microsystem viewpoint of Bronfenbrenner's Bioecological Model. The study stresses the gap in understanding the pivotal role of teachers' learning ecology perspectives in improving students' English-speaking skills. This study applied a qualitative research methodology with a phenomenological design to study teachers' perceptions of learning ecology. Data was collected through semi-structured interviews with EFL Instructors in Indonesia with a triangulation of data sources to ensure validity and reliability. For data analysis, thematic analysis was used to search for reoccurring themes. The findings revealed that EFL instructors in Indonesia perceive learning ecology as highly influential for speaking skills. To take maximum advantage of it, instructors in Indonesia apply strategies like interactive learning and sufficient exposure. However, they also shed light on challenges in terms of the unavailability of native speakers. Their reflection on the microsystem proposed bringing EFL speaking to a more practical context. The findings of this study contribute to our understanding of how teachers may construct a learning environment that fosters the development of ESL learners' speaking skills, influenced by Bronfenbrenner's Bioecological Model’s microsystem layer.